(untitled) (Altre Modernità, 2011)
In the “realismo mágico” as latin-american literary aesthtic, magic was related to metaphorical imagination, especially trough the hyperbole, but there’s also a narrative expressing cultural elements of a sociaty based on magic, because of faith and rituals still in use in daily life. It’s tha case of the cuban narrator Mayra Montero. In the novel Del mismo rojo de su sombra the protagonists, man and woman, contend the power of the haitian voodu, in a proper fight where the body plays a foundamental role in the developp of rituals. The femal body fight both in social and gender sense. Althoug she falls dead, in a simbolic level the woman wins agaisnt the negative power of the bokor, the man, by imposing herself. We analize here the way magic elements are no more only literary aesthetic, but the reality of a lively culture represented in the novel, and the way how that magic is practised by the female body, one that gains emancipation in a personal and social level in the haitian culture.